Pemanfaatan Media Sosial Tiktok Untuk Pemasaran Bisnis Digital Sebagai Media Promosi - Adi S Kurniawan; Raja Fitriana; Masayu Vrisaliani; Natasya Saffa Adesti; Suci Alya Rahmadhani (Politeknik Raflesia Press, 2025)
Utilizing TikTok social media as a promotional medium in digital business marketing has become a significant innovative strategy in the digital era. This research aims to analyze the effectiveness of TikTok in creasing brand awareness, audience interaction, and sales conventions, by comparing local (Indonesian) and global approaches. The research method uses qualitative analysis through literature sources in two geographical contexts. The research results show that TikTok is able to massively increase the visibility of digital businesses through creative content, collaboration with influencers, and the use of paid advertising features such as hashtag challenges include rapidly changing algorithm dynamics and intense content competition. This research concludes that the success of Tiktok marketing strategies depends on cultural adaptation, content creativity, and the use of analytical data for campaign optimization. This research provides practical implications for digital business actors to maximize TikTok’s potential as an effective and affordable promotional media.